Heroism of a native of Chuvashia I. G. Meshakov during the crossing of the Southern Bug River in March 1944 - Efimov L. A. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
in the article, the author, based on the extensive use of archival documents introduced into scientific circulation for the first time, as well as published literature in regional historiography, objectively highlights the military exploits of I. G. Meshakov, a native of the village of Basurmanovo in the Morgaush municipal District of Chuvashia, on the fronts of the Great Patriotic War, who was awarded the title Hero of the Soviet Union in March 1944 when crossing the Southern Bug River.
Keywords: Великая Отечественная война; Чувашия; Great Patriotic War; Chuvashia; Герой Советского Союза; Hero of the Soviet Union; Мешаков И.Г.; деревня Басурманы; 1944 год; река Южный Буг; Basurmany village; 1944; Yuzhny Bug River; Meshakov I.G